DYNAMICS OF INSULIN-LIKE GROWTH FACTOR-1 (IGF-1) IN CHILDREN AFTER AB0-INCOMPATIBLE LIVER TRANSPLANTATION - O.P. Shevchenko; O.M. Tsirulnikova; I.E. Tsirulnikova; R.M. Kurabekova; G.A. Olefirenko; O.I. Stepanova; S.V. Gautier (Вестник трансплантологии и искусственных органов)
It is shown that liver transplantation (LT) from donor with incompatible blood type (AB0i) may be effective and safe, but the impact of such operation upon the various systems of the body has not been investigated yet. Insulinlike growth factor-1 (IGF-1) is synthesized in the liver and mediates the action of growth hormone. The level of IGF-1 is a marker of the processes of cell proliferation and tissue regeneration. Aim. To evaluate levels of IGF-1 in children-recipients with liver transplant from AB0i (incompatible) and AB0c (compatible) donors.Materials and methods. 140 children aged 3 to 36 (19,5 ± 16,5 months) with congenital diseases of the hepatobiliar system, 58 of them boys, were surveyed. All patients underwent transplantation of left lateral liver sector from living related donors: 111 children were transplanted with fragment of the liver from AB0c donors, 29 – from AB0i donors; in 10 children with AB0i liver before and/or after LT operation anti-group antibodies (anti-A/B) were revealed. The concentration of IGF-1 was determined by ELISA using specifi c kits (Immunodiagnostic System, USA) in samples of blood plasma, which were received up to a month and a year after a liver transplant.Results. Average level of IGF-1 21,0 ± 29,5 μg/l in patients before LT was signifi cantly lower than in healthy children (52,2 ± 26,3 μg/l, p < 0,001) and did not vary in children, having received later a piece of liver from a compatible (AB0c) donor and from donor AB0i (23,5 ± 30,9 and 21,2 ± 23,2 μg/l respectively, p = 0,70). In patients with anti-A/B prior to surgery average level of IGF-1 was not different from that of the patients without antibodies (32,6 ± 27,6 and 22,3 ± 29,6 μg/l respectively, p = 0,4). One month after LT level of IGF-1 has increased both in the general group, and in patients with AB0c and AV0i liver (92,1 ± 77,8 and 131,2 ± 106,7 μg/l respectively, p = 0,09). The level of IGF-1 was not varied in the group with antibodies (152,5 + 150,4 μg/l) and without them (95,9 ± 77,0 μg/l). A year after LT the average level of IGF-1 in recipients of AV0c and AV0i liver was not varied and was signifi cantly higher than before LT (82,0 + 60,7 and 91,2 ± 77,8 μg/l, p < 0,005 and p = 0,03 respectively). The content of IGF-1 in patients with anti-A/B and without them (104,7 ± 67,5 and 84,7 ± 63,7 μg/l respectively) also did not differ.Conclusion: the results of our studies have shown that restoration of the level of IGF-1 is not dependent on transplantation of compatible or incompatible blood type liver, as well as on the availability of anti-group antibodies.